The Influence of Learning Motivation on Learning Outcomes of Islamic Religious Education on the Material of Living Peacefully in Togetherness of Class V Students in Jantur Village, Muara Muntai - Norhalizah, Siti; Hidayat, Taufik (Universitas Pahlawan Tuanku Tambusai, 2026)
This research is motivated by the learning outcomes of Islamic Religious Education (PAI) of fifth-grade elementary school students in Jantur Muara Muntai Village who are still on the material of Living in Peace in Togetherness, suspected to be influenced by learning motivation that needs to be analyzed. The purpose of the study is to analyze the influence of learning motivation on PAI learning outcomes. This type of quantitative research with an ex post facto design uses descriptive and inferential methods. The population is 77 fifth-grade students from three elementary schools, a sample of 30 students with proportional random sampling. The instruments in the form of a learning motivation questionnaire (25 Likert scale items) and a learning outcome test (36 multiple-choice questions), were analyzed using descriptive statistics and simple linear regression through SPSS 25.0. The results show high learning motivation (mean = 72.65), moderate learning outcomes (mean = 18.77), with a regression equation of Ŷ = 13.492 + 1.257X, p = 0.001 0.05, and R² = 0.888. The conclusion states that learning motivation has a significant positive effect on PAI learning outcomes, explaining 88.8% of the variability.